Daya Saing Kopi Arabika Bali Sebagai Komoditi Ekspor - DEWI, IDA AYU LISTIA; DJELANTIK, AAA WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Competitiveness of Bali Arabica Coffee as an Export Commodity This study aims to examine the competitiveness of Balinese coffee from comparative advantage, and identify factors supporting the competitiveness of Balinese Arabica coffee. The research location was carried out in Catur Village, Kintamani District, Bangli Regency. Determining the location of research with a purpose method. Comparative advantage is seen from the value of the RCA index and competitive advantage is identified based on the Berlian Porter approach. The results of the analysis show that Bali coffee has low comparative competitiveness as shown by the RCA value of Bali coffee for 5 consecutive years < 1. There are several factors that can increase the competitive advantage of Balinese Arabica coffee, according to Berlian Poter's approach, including: 1. Intermediate factor requirements other natural resources that support Bali Arabica coffee to become IG products. Experienced human resources more than 20 years. 2. Demand from foreign markets has decreased due to covid but the domestic market has increased rapidly. 3. Competition between coffee-producing countries makes each producer have to maintain the quality of its product. 4. There are many government roles related to regulations from upstream to downstream industries. The conclusion that can be drawn is that although the comparative advantage of Balinese coffee has low competitiveness, it will be covered by competitive advantages, especially Bali Arabica coffee which has a very good taste which has been registered as a Geographical Indication product.